2021
DOI: 10.3390/bs11050061
|View full text |Cite
|
Sign up to set email alerts
|

Death Anxiety in Social Workers as a Consequence of the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has affected all social spaces, conditioning our daily routines, including those at work. All professions have been affected by stressful situations and anxiety in the proximity’s face of death generated by the pandemic. In this context, some professionals have emerged as essential, as social workers, acting in extreme situations in the face of increased demands and social uncertainty arising from the health crisis. The present study aimed to determine the levels of anxiety about death am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
(47 reference statements)
1
19
1
Order By: Relevance
“…A fear of contamination is also closely linked to death anxiety, especially fear of the death of loved ones. Several studies have shown that this type of fear is very strong during the COVID-19 pandemic [69,70]. In our case, a very significant relationship emerged at the correlational level, but not in the regression models.…”
Section: Discussioncontrasting
confidence: 63%
“…A fear of contamination is also closely linked to death anxiety, especially fear of the death of loved ones. Several studies have shown that this type of fear is very strong during the COVID-19 pandemic [69,70]. In our case, a very significant relationship emerged at the correlational level, but not in the regression models.…”
Section: Discussioncontrasting
confidence: 63%
“…Although acute respiratory distress syndrome (ARDS) is the most challenging and harmful condition resulting in the serious course of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection, the affliction of the cardiovascular, 314,315 digestive, 317 and CNSs, among others, 318 are rather frequent complications. Moreover, stress and anxiety were disclosed in different groups of health care providers, such as dental practitioners, 319 other healthcare workers, 319,320 health profession students, 322 social workers 323 and in patients afflicted by COVID‐19 324 . The underlying reasons for mental disturbances involve fear of exposure to infection, proximity to death generated by the pandemic, extreme working demands, economic uncertainty, disruption of social life, insufficient knowledge of the disease and SARS‐CoV‐2‐induced physical disturbances in terms of endothelial inflammation, microvascular thrombosis, ischemia from pulmonary damage and multiple organ dysfunctions 318,319,321,323 .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, because there is no baseline assessment of hopelessness or fear of death, we cannot have absolute certainty that these latter are anchored to COVID-19. However, in this context, a recently published paper relates death anxiety among social workers as a consequence of the COVID-19 pandemic [36]. Lastly, the PTSD symptoms have been investigated with a general evaluation scale, not specifically related to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in palliative care settings found that these feelings can be experienced by healthcare workers with the development of personal fear of death first, and later post-traumatic stress symptoms [34,35]. In the context of the Covid-19 pandemic, in light of many losses and ultimately the same feelings analogous to those that delineate the hopelessness concept [36], we hypothesized in this exploratory study that precisely the latter could act as a mediator with post-traumatic stress symptoms.…”
Section: Introductionmentioning
confidence: 95%